Introduction: Law's Theatrical Presence + Contributions & Acknowledgements - Marett Leiboff; Sophie Nield (Law Text Culture, 2010)
This special issue of Law Text Culture explores law through the lens of theatrical theory and reads theatre through the paradigm of law. This unique interaction between the disciplines of theatre studies and law has brought together an extraordinary array of scholars working at the interstices of these fields, and delivers, we hope, a fascinating range of perspectives that will serve as both introduction to, and illustration of, the richness of this disciplinary exchange.